Exploring the Agency Cost of Debt: Evidence from the ISS Governance Standards - Pornsit Jiraporn (2018)
Corporate governance is usually viewed in the context of strengthening shareholder rights and enhancing shareholders' welfare. However, the impact of corporate governance on bondholders is much less understood. We explore how corporate governance influences the cost of debt financing. Using broad governance metrics encompassing fifty governance attributes reported by The Institutional Shareholder Services (ISS), we document that stronger corporate governance is associated with a higher cost of debt. As governance strengthens by one standard deviation, the cost of debt rises by as much as 11 %. The results are robust even after controlling for both firm-specific and issue-specific characteristics. Our results are important because they suggest that corporate governance has a palpable effect on critical corporate outcomes such as credit ratings and bond yields. More importantly, we show that, while corporate governance may mitigate the agency conflict between managers and shareholders, it appears to exacerbate the agency conflict between shareholders and bondholders (the agency cost of debt). © 2012 Springer Science+Business Media, LLC.